2020
DOI: 10.1002/ece3.6291
|View full text |Cite
|
Sign up to set email alerts
|

Intercolony variation in foraging flight characteristics of black‐headed gulls Chroicocephalus ridibundus during the incubation period

Abstract: Using GPS loggers, we examined the influence of colony, sex, and bird identity on foraging flight characteristics of black‐headed gulls Chroicocephalus ridibundus during the incubation period. We studied tracks of 36 individuals breeding in one urban and two rural colonies in Poland. Birds from both rural colonies performed the furthest flights (mean max distance 8–12 km, up to 27 km) foraging mainly in agricultural areas. Gulls from the urban colony performed shorter flights (mean 5 km, up to 17 km) visiting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Despite our expectations, we found similar prevalence of Campylobacter in black-headed gulls breeding in urban (4.3%) and rural (3.8%) habitats. Our previous study has shown that birds from the urban colony in Bydgoszcz forage mainly on the territory of the city and in its immediate vicinity, while birds from non-urban colonies tend to avoid this type of habitat during foraging flights (Jakubas et al 2020 ). We predicted that urban birds may be exposed to more sources of Campylobacter than rural birds, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Despite our expectations, we found similar prevalence of Campylobacter in black-headed gulls breeding in urban (4.3%) and rural (3.8%) habitats. Our previous study has shown that birds from the urban colony in Bydgoszcz forage mainly on the territory of the city and in its immediate vicinity, while birds from non-urban colonies tend to avoid this type of habitat during foraging flights (Jakubas et al 2020 ). We predicted that urban birds may be exposed to more sources of Campylobacter than rural birds, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, to test habitat use specialisation for each behaviour (foraging, resting, or travelling) at an individual and age group level, we calculated a Diversity Habitat Use 11 index (DHU) based on Shannon index [49]: 𝐷𝐻𝑈 = − ∑ 𝑝 𝑖 ln (𝑝 𝑖 ) ln (7) , where pi is the proportion of positions in each habitat. This index ranges from 0 meaning that they use only one habitat, to 1 where they equally use all the habitats.…”
Section: Diversity Of Habitat Usementioning
confidence: 99%
“…In this case, values near 0 indicate that individuals do not select the same habitats every day and values equal to 1 indicate that each individual select the same habitats during the non-breeding season. We calculated the index using the kripp.alpha() function of 'irr' package [48] [49]: 𝐷𝐻𝑈 = − ∑ 𝑝 𝑖 ln (𝑝 𝑖 ) ln (7) , where pi is the proportion of positions in each habitat. This index ranges from 0 meaning that they use only one habitat, to 1 where they equally use all the habitats.…”
Section: Repeatability Of Habitat Usementioning
confidence: 99%
“…In case of danger from predators, the pair jointly defend the colony, but often leave it temporarily (Indykiewicz 2015). During incubation, they forage mainly near the colony, depending on the colony size and environment (Jakubas et al 2020). Some authors suggest exclusively diurnal activity of this species (Chandler 1983;Wikelski et al 2006;Evans et al 2018).…”
Section: Introductionmentioning
confidence: 99%